Mate‐finding Allee effects can be exacerbated or relieved by sexual cannibalism. Issue 7 (18th May 2020) - Fisher, Adam M.; Cornell, Stephen J.; Holwell, Gregory I.; Price, Tom A. R.
Abstract: Allee effects occur when individual or population survival decreases due to populations being small or sparse. A key mechanism underlying Allee effects is difficulty in finding mates at low densities. Species may be particularly vulnerable to mate‐finding Allee effects if females rely on an abundance of males to reproduce successfully. In sexually cannibalistic species, females may consume males before or after copulation, potentially reducing the supply of males to the point where a mate‐finding Allee effect occurs. In this study, we investigate the extent to which sexual cannibalism can modulate mate‐finding Allee effects, and the conditions under which sexual cannibalism is likely to be particularly detrimental to population viability. We created an individual‐based model that tracked specific females throughout the breeding season and used extinction risk and per capita growth rate to measure the strength of the Allee effects. We varied both founder population size and mate encounter rate independently of each other to expose the mechanism driving the Allee effects. We also analysed how cannibalism‐derived female fecundity benefits affected extinction risk. We found that sexual cannibalism could lead to high extinction risk, particularly when cannibalism occurred before copulation, founder population size was small and mate encounter rates were low. However, post‐copulatory cannibalism reduced extinction risk, if cannibalism increased female fecundity enough. We found that there were strong threshold effects, in which small changes in encounter rate could strongly alter population extinction risk. We find that sexual cannibalism is likely to negatively impact population survival as population size and mate encounter rate decrease. This may be exacerbated if male quality declines and female hunger increases in declining populations. As many top invertebrate predators, such as spiders and mantises, are sexually cannibalistic, this may have ecosystem‐wide impacts. We also suggest that other reproductive behaviours, such as rejecting all but high‐quality mates or requiring multiple mates to ensure fertility, are also likely to cause mate‐finding Allee effects when habitat quality degrades. Abstract : Using individual‐based models the authors have shown that sexual cannibalism can exacerbate the increases in extinction risk associated with reductions in population size and density. However, cannibalism can also promote population survival if it occurs after copulation. This highlights the importance of considering species‐specific reproductive behaviour when predicting ecology.